Microwave catalytic effect: a new exact reason for microwave-driven heterogeneous gas-phase catalytic reactions. Issue 3 (15th December 2015) - Xu, Wentao; Zhou, Jicheng; Su, Zhiming; Ou, Yingpiao; You, Zhimin
Abstract : The microwave catalytic effect (lowering of activation energy) under microwave irradiation results in NO conversion exceeding that realized through conventional heating. Abstract : Direct catalytic NO decomposition was drastically enhanced under microwave irradiation. Such enhancements would NOT be simply caused by the "hot-spots" hypothesis, as the apparent activation energy decreased greatly under microwave irradiation. Therefore, the microwave catalytic effect rather than solely the "hot-spots" hypothesis is the new exact reason for these enhancements.